Pullout Tests on Post-installed Bonded Anchors in Ultra-high Performance Fiber Reinforced Concrete. Issue 3 (3rd July 2019) - Delhomme, Fabien; Brun, Michael
ABSTRACT: An experimental study was completed on the behavior on post-installed bonded anchors in ultra-high performance fiber reinforced concrete with a compressive strength higher than 150 MPa. The aim was to analyze the failure mechanisms in static pullout tests. The diameter of the tested anchors was 12 mm and the studied parameters were the embedment depth, the edge distance and the state of cracking of the concrete block. In case of tests without edge effect in uncracked concrete, a combined pullout and concrete cone failure occurred for an embedment depth lower than 60 mm. The recorded mean bond stress was 32.5 MPa for uncracked concrete and 16.3 MPa for cracked concrete with a crack width of approximately 1 mm. A splitting failure was observed for shallow embedment and for edge distances lower than 60 mm. For this tested special anchor system, the increase in tensile strength provided by the metallic fibers enhances the tensile behavior of anchors in comparison to normal strength concrete. It is necessary to adapt the design codes developed for normal strength concrete in order to have more accurate and reliable prediction methods.